PATIENT PREFERENCES IN UTILIZING DIGITAL MARKETING FOR HOSPITAL SELECTION: STUDY AT A PRIVATE HOSPITAL MY IN EAST JAVA - Wulandari, Retno; Holipah, Holipah; Ghofir, Abdul (Journal of Community Health and Preventive Medicine, 2025)
Hospital marketing through social media is proven to influence patients' interest in visiting the hospital. This study aims to assess patients' preferences in the use of digital marketing and their decision to visit Private Hospital MY. This study used a descriptive method. Data were collected using a questionnaire with a 5-level Likert scale measurement on 27 outpatients and inpatients during August 2024. The questionnaire contains patient perspectives on the role of digital media in helping to choose a hospital to get health services. Data were analyzed using descriptive statistics. The results showed that all respondents agreed that information through digital advertising played an important role in choosing a hospital. Most respondents (67%) had seen digital advertisements for Private Hospital MY. However, only a few respondents (7%) stated that they visited Private Hospital MY because they saw the advertisement. Most of them visited Private Hospital MY because of family recommendations and hospital facilities. The results of this study can be used as a basis for hospital management to develop hospital marketing initiatives by optimizing digital marketing in increasing the number of patient visits to Private Hospital MY.